Diallel Analysis of Diverse Maize Germplasm Lines for Agronomic Characteristics. Issue 6 (1st November 2014) - Henry, W. Brien; Blanco, Michael H.; Rowe, Dennis E.; Windham, Gary L.; Murray, Seth C.; Williams, W. Paul
ABSTRACT: Diverse, novel maize ( Zea mays L.) germplasm from the Genetic Enhancement of Maize (GEM) Project and aflatoxin‐resistant and aflatoxin‐susceptible maize lines were used as parents to produce a diallel cross. This manuscript documents the agronomic performance of the progeny of the diallel cross. Nine GEM germplasm lines and six known resistant and susceptible lines were selected as parents of a diallel cross that was evaluated over 2 yr at Mississippi State, MS, and 1 yr at College Station, TX. Mp317, Mp494, NEI9008, and GEMN‐0130 had positive and significant GCA effects for yield in at least two of the three environments. This is especially useful because prior research suggested that both Mp494 and GEMN‐0130 also reduce aflatoxin accumulation. Of the GEM lines evaluated, NEI9008 was the best source for enhanced yield with significant and positive GCA values across all three environments. Mp313E × GEMN‐0157 yielded well across all environments with an additional benefit of relatively low aflatoxin accumulation in the Mississippi environments. Because the GEM lines evaluated in this diallel cross have a distinctly different genetic background than the aflatoxin‐resistant Mississippi inbreds, NEI9008 and GEMN‐0130 (improved yield), GEMS‐0002 and GEMS‐0074 (earlier maturity by 3 to 4 d), CUBA117, GEMS‐0030, GEMN‐0071, GEMS‐0100 (reduced plant height 0.1 to 0.2 m), GEMN‐0157, NEI9008, GEMS‐0002, and GEMS‐0074 (reduced height by 0.3 to 0.4 m) should be useful sources of alleles for pyramiding improved yield, earlier maturity, and shorter plant heights into improved breeding lines.